A mitochondria-tracing fluorescent probe for real-time detection of mitochondrial dynamics and hypochlorous acid in live cells. (May 2022) - Zhu, Nansong; Guo, Xiaolei; Chang, Yulei; Shi, Zhan; Jin, Long Yi; Feng, Shouhua
Abstract: Mitochondrial dynamics and hypochlorous acid (HOCl) are involved in many physiological and pathological processes. Therefore, the development of real-time analysis tools for biological studies involving mitochondrial dynamics and HOCl is highly significant. Herein, we report a fluorescent probe, RIC, consisting of rhodamine, imidazolium salt, and coumarin, which has high selectivity and sensitivity toward HOCl. RIC has an inherently blue fluorescence signal and can be anchored in mitochondria, which enables it to reveal changes in mitochondrial dynamics. This mitochondria-anchoring characteristic also facilitates the real-time detection of HOCl in mitochondria. To our knowledge, RIC is the first probe to detect mitochondrial dynamics and HOCl in real time. The detection limit of HOCl is as low as 3.8 nM, and RIC analyzes endogenous and exogenous HOCl in live cells. The detection capacity is pH-insensitive in the physiological pH range of mitochondria, and the HOCl-sensing process is completed within seconds in cuvettes. Furthermore, we prove that the molecular design strategy provides a general synthetic method for constructing new multifunctional probes for HOCl. Graphical abstract: Image 1 Highlights: The first probe that can simultaneously detect mitochondrial dynamics and HOCl. A general synthetic method for multifunctional HOCl probes. Real-time detection of changes in mitochondrial morphology and HOCl. High selectivity and sensitivity, fast response, and mitochondrial pH insensitivity toward sensing HOCl.